2016
DOI: 10.1186/s13104-016-1884-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the failure of first and second-line antiretroviral therapies therapy, a case control study in Cambodian HIV-1 infected children

Abstract: BackgroundLittle is known about the efficacy of first and and second-line antiretroviral therapies (ART) for HIV-1 infected children in resource limited Southeast Asian settings. Previous studies have shown that orphans are at a higher risk for virological failure (VF) in Cambodia. Consequently most of them required transfer to second-line ART. We assessed the factors associated with VF among HIV-1 infected children who were either under first-line (mostly 3TC + D4T + NVP) or under second-line (mostly ABC + DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…This study showed that the baseline CD4 count was not a predictor of treatment failure. This was in contrast with the result of studies done in Addis Ababa, 18 Cambodia 29 and Thailand, 33 but consistent with the study conducted among Ugandan children. 28 This might be due to the high public health advocated approach to ART nowadays, which substantially increased the awareness of healthcare providers and caregivers.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study showed that the baseline CD4 count was not a predictor of treatment failure. This was in contrast with the result of studies done in Addis Ababa, 18 Cambodia 29 and Thailand, 33 but consistent with the study conducted among Ugandan children. 28 This might be due to the high public health advocated approach to ART nowadays, which substantially increased the awareness of healthcare providers and caregivers.…”
Section: Discussionsupporting
confidence: 79%
“… 19 Moreover, this study showed a lower failure rate than other studies done in Africa, for example Nigeria (18.8%), 13 Uganda (34%), 28 a combined study from Mozambique-Uganda (29%) 16 and Cambodia (8.6%). 29 However, the result was higher than the result in India of 5.1%. 30 This may be due to improvements of healthcare services in the later periods of follow-up as compared with earlier periods.…”
Section: Discussionmentioning
confidence: 63%
“…This result was consistent with previous studies conducted in Asia and Sub‐Saharan Africa (16.4%), 34 Rwanda (17%) 35 and Gondar (14.7%) 20 but higher than studies conducted in Asia‐Pacific sites (7%), 36 Cambodian (7%), 37 Malawi (9.3%), 38 and in Ethiopia (13.6%) 14 and it was Lower than studies conducted in Thailand (49%), 39 Vietnam (22.8%), 10 Uganda (23%), 40 and Ethiopia (25.11%) 41 and (18.4%) 42 . The higher magnitude of VF in this study could be attributed to the difference in the studied populations which were the inclusion of individuals who were on PI‐based regimen only or studied children or adults above the age of 18 and the use of clinical and immunological criteria to define TF which are less specific and sensitive measures 14,36–38 . The low prevalence of VF in this study might be due to those studies involved only PI‐based children, the use of death as an additional criterion to define TF, exclusion of patients who did not have baseline viral load at SLART initiation and who had regimen change 10,39–42 …”
Section: Discussionsupporting
confidence: 93%
“…11 Studies show that virological failure occurs due to factors, such as being male in gender, [12][13][14][15] age < 3 years, [16][17][18] being orphaned, 14,15 non-disclosure, 15,19 poor adherence, 15,17,20,21 has not being on ART for a long period 13 and take ART suboptimal. 12 In addition, opportunistic infections, [15][16][17]19,20,22,23 malnutrition, 14,16 were WHO stage 3 and 4, 15,24 lower CD4 count (Cells/ mL), 12,15,16,20,[24][25][26] initial viral load >1000 copies/ mL, 21,27 D4T/3TC/NVP based regimen, 21,22,[28][29][30] regimen change, 14,15 longer duration on ART, 15,31 treatment interruption, 12,…”
Section: Introductionmentioning
confidence: 99%